The impact of climate change on urban woody plants: The case of Velenje, 2008–2023 - Pajk, Barbara; Dolejši, Nataša (Journal for Geography, 2024)
The paper examines the impact of climate change on urban trees in public areas of the Municipality of Velenje between 2008 and 2023. The aim is to determine how many and which tree species have disappeared and which are still growing, and to analyze the reasons for these changes. The results show that climate change, extreme weather events, and urbanization have significantly affected the fluctuation in the number of trees of represented species in public areas of the municipality. The study emphasizes the importance of green infrastructure for improving microclimatic conditions and the quality of life in urban environments. It highlights the need for sustainable planning and management of trees, which includes planting new trees and preserving existing ones. The report also includes updates to the tree register, which is accessible online.